Choline acts during preimplantation development of the bovine embryo to program postnatal growth and alter muscle DNA methylation. Issue 10 (17th September 2021) - Estrada‐Cortés, Eliab; Ortiz, William; Rabaglino, Maria B.; Block, Jeremy; Rae, Owen; Jannaman, Elizabeth A.; Xiao, Yao; Hansen, Peter J.
Abstract: The preimplantation period of embryonic development can be a key window for programming of postnatal development because extensive epigenetic remodeling occurs during this time. It was hypothesized that modification of one‐carbon metabolism of the bovine embryo by addition of the methyl‐donor choline to culture medium would change postnatal phenotype through epigenetic modification. Embryos produced in vitro were cultured with 1.8 mM choline chloride or control medium. Blastocysts were transferred into females and pregnancy outcomes and postnatal phenotype of the resultant calves determined. Exposure of embryos to choline increased gestation length and calf birth weight. Calves derived from choline‐treated embryos were also heavier at weaning and had increased ratio of body weight to hip height than control calves. Choline altered muscle DNA methylation of calves 4 months after birth. A total of 670 of the 8149 CpG examined were differentially methylated, with the predominant effect of choline being hypomethylation. Among the genes associated with differentially methylated CpG were ribosomal RNAs and genes in AMPK, mTOR, integrin, and BEX2 canonical pathways and cellular functions involved in growth and proliferation. Results demonstrate that provision of the methyl‐donor choline to the preimplantation embryo can alter its developmental program to increase gestation length, birth weight, and weaning weight and cause postnatal changes in muscle DNA methylation including those associated with genes related to anabolic processes and cellular growth. The importance of the nutritional status of the embryo with respect to one‐carbon metabolism for ensuring health and well‐being after birth is emphasized by these observations.